Knotting of a Urinary Catheter and Ureteric Stent: A Unique Complication and Management Solution - H. Logan; K. Lockhart; P. Chong (Case Reports in Urology)
Conclusion: Endoscopic techniques such as the use of a stone crusher may be beneficial for the removal of difficult and complex catheter knots as demonstrated in this case. Catheter knotting should always be considered if the functioning or attempted removal of the catheter is abnormal and timely referral to a urologist is made.